Предмет: Алгебра,
автор: Аноним
помогите пожалуйста.
Приложения:
![](https://files.topotvet.com/i/24a/24a79fa0b7fc83e85284285b72eebcd0.jpg)
Ответы
Автор ответа:
0
Вот само решение, сорри если криво
Приложения:
![](https://files.topotvet.com/i/9ee/9ee1c1d4f76ded87d6e6fa7c69edc581.png)
Автор ответа:
0
(2√2+3)*√(2√2-3)^2)=
= - (2√2+3)(2√2-3)= -(8-9)=1
= - (2√2+3)(2√2-3)= -(8-9)=1
Похожие вопросы
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: omoldoshovaeliza
Предмет: Литература,
автор: nalivaikodaria08
Предмет: Алгебра,
автор: Olya02071
Предмет: Математика,
автор: zyrf0